Shanghai Studies: An evolving academic field - Jin, Yan (History compass, 2018)
The field of Shanghai Studies has a history of more than a century. It evolves along with the unfolds of modern history of Shanghai. The city's dramatic growth in the late 19th century aroused early scholarly attempts in writing the history of the city. In the following half century, however, due to the chaotic socio-political context, the studies of Shanghai had never really taken off. After 1949, when the Chinese communists took power, the studies of Shanghai was forced to conform with major political themes of modern Chinese history. Broad political ideas always superseded local history. It was not until the late 1980s, when the study of Shanghai history began to surge and immediately grew into one of the most vibrant and prolific subfields of historical studies. It has no sign of crescent so far, with an ever growing research community and the openness towards new perspective and methodology.